Visual inertial odometry and lidar inertial odometry for mobile robot - Henawy, John Farid Nasry (Nanyang Technological University, 2021)
Municipal infrastructure inspection and maintenance are vital to keep the integrity and safe operation of large-scale infrastructure such as pipelines, bridges and tunnels. For example, regular inspection and assessment of tunnels are essential to prevent any possible leakage or worse, collapse. Inspection of deep sewerage tunnels is even more challenging because of their complex environment where such tunnels are not only difficult to reach, they may also have dangerous bacteria and microorganisms and the sewer gas would also have mixture of flammable and toxic gases such as hydrogen sulphide, methane, ammonia and sulphur dioxide. In Singapore, deep tunnel sewerage system (DTSS) is 6 m in diameter and located about 20 to 50 m underground.